2019
DOI: 10.1093/jjco/hyz066
|View full text |Cite
|
Sign up to set email alerts
|

The effect and safety of immune checkpoint inhibitor rechallenge in non-small cell lung cancer

Abstract: Introduction Immune checkpoint inhibitors (ICIs) have demonstrated long survival for the treatment of advanced non-small cell lung cancer (NSCLC). However, the effect and safety of ICI rechallenge have not been fully evaluated. The aim of this study was to investigate the efficacy and safety of ICI rechallenge in NSCLC patients. Methods We defined ‘rechallenge’ as re-administration of ICIs for patients who were previously tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 12 publications
3
53
2
1
Order By: Relevance
“…There was a clinical benefit rate of 38% in patients with anti-PD-(L)1 re-challenge, suggesting that patients can respond to anti-PD-(L)1 re-treatment. Our results mirror other RWD results of anti-PD-(L)1 re-challenge where disease control rate has varied from ~ 20% to a bit over 40% with NSCLC patients (Fujita et al 2020;Niki et al 2018;Watanabe et al 2019). A recent retrospective study on melanoma patients treated mainly outside clinical trials, whose anti-PD-1 treatment had been discontinued for any reason, reported a response rate of only 14.7% of single-anti-PD-1, and ~ 25% to combination-ICI therapy re-challenge, while there was no causality between the initial best overall response to re-treatment response (Betof Warner et al 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was a clinical benefit rate of 38% in patients with anti-PD-(L)1 re-challenge, suggesting that patients can respond to anti-PD-(L)1 re-treatment. Our results mirror other RWD results of anti-PD-(L)1 re-challenge where disease control rate has varied from ~ 20% to a bit over 40% with NSCLC patients (Fujita et al 2020;Niki et al 2018;Watanabe et al 2019). A recent retrospective study on melanoma patients treated mainly outside clinical trials, whose anti-PD-1 treatment had been discontinued for any reason, reported a response rate of only 14.7% of single-anti-PD-1, and ~ 25% to combination-ICI therapy re-challenge, while there was no causality between the initial best overall response to re-treatment response (Betof Warner et al 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Due to the unique mechanism of anti-PD-(L)1 therapies, some patients experience long-lasting and durable responses, while a growing data shows that ICI re-challenge can bring meaningful clinical benefit to patients whose anti-PD-(L)1 therapy has been discontinued (Blasig et al 2017;Fujita et al 2020;Iivanainen and Koivunen 2019;Niki et al 2018;Watanabe et al 2019). Determination of the optimal Antti Tikkanen and Sanna Iivanainen have contributed equally to the study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ORR, DCR, and PFS of atezolizumab rechallenge after refractory anti-PD-1 antibodies for 18 patients with NSCLC were 0%, 38.9%, and 2.9 months, respectively [17]. Another report showed that ORR, DCR, and PFS values of ICI rechallenge in 14 patients with ICI refractory tumors were 7.1%, 21.4%, and 1.6 months, respectively [7]. Our current observations showed that ORR, DCR, PFS, and OS values of ICI rechallenge in 35 patients with NSCLC were 2.9%, 42.9%, 2.7 months, and 7.5 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is warranted to identify predictive clinical markers for the effectiveness of ICI rechallenge. Previous retrospective studies regarding ICI rechallenge have analyzed only limited numbers of NSCLC patients [7,8]. Hence, little is currently known regarding the effectiveness and tolerability of ICI rechallenge after disease progression following initial ICI treatments.…”
Section: Introductionmentioning
confidence: 99%
“…1 The effect of immune checkpoint inhibitor (ICI) rechallenge after progression during the first ICI treatment is also thought to be limited. 2 However, there is no large prospective study to confirm the efficacy of ICI rechallenge, nor is there a predictive marker to identify a patient in whom ICI rechallenge is effective. 3 We have encountered a patient with NSCLC who showed a drastic response to rechallenge with nivolumab after acquisition of resistance to the first nivolumab treatment.…”
mentioning
confidence: 99%